PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN PROMOSI TERHADAPKEPUTUSAN PEMBELIAN PRODUK MAKANAN DAN MINUMAN PADA SENSE CAFE BATAM - Punuh, Jeini; Purba, Daris (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of service quality, product quality and promotion on purchasing decisions for food and beverage Sense Café Batam. The type of research used is descriptive quantitative, which is research data obtained fromquestionnaires and processed in the SPSS application. The research objects which are independent variables are service quality (X1), product quality (X2), promotion (X3) and purchasing decisions (Y) as the dependent variable. The population of this study were all consumers and visitors to Sense Café with a total of 150 respondents. The sampling method used is saturated sampling, where the sampling uses the entire population. The results showed that the effect of service quality and product quality had a significant effect on purchasing decisions, while promotions had no effect on purchasing decisions. R square 73.1%. from these results it can be concluded that the variables of service quality, product quality and promotion simultaneously influence the purchasing decision variable.